Meta-analysis and field synopsis of genetic variants associated with the risk and severity of acute pancreatitis. Issue 1 (3rd February 2020) - van den Berg, F. F.; Kempeneers, M. A.; van Santvoort, H. C.; Zwinderman, A. H.; Issa, Y.; Boermeester, M. A.
Graphical Abstract: Abstract: Background: Genetic risk factors can provide insight into susceptibility for acute pancreatitis (AP) and disease progression towards (infected) necrotizing pancreatitis and persistent organ failure. The aim of the study was to undertake a systematic review of the genetic evidence for AP. Methods: Online databases (MEDLINE, Embase, BIOSIS, Web of Science, Cochrane Library) were searched to 8 February 2018. Studies that reported on genetic associations with AP susceptibility, severity and/or complications were eligible for inclusion. Meta-analyses were performed of variants that were reported by at least two data sources. Venice criteria and Bayesian false-discovery probability were applied to assess credibility. Results: Ninety-six studies reporting on 181 variants in 79 genes were identified. In agreement with previous meta-analyses, credible associations were established for SPINK1 (odds ratio (OR) 2·87, 95 per cent c.i. 1·89 to 4·34), IL1B (OR 1·23, 1·06 to 1·42) and IL6 (OR 1·64, 1·15 to 2·32) and disease risk. In addition, two novel credible single-nucleotide polymorphisms were identified in Asian populations: ALDH2 (OR 0·48, 0·36 to 0·64) and IL18 (OR 1·47, 1·18 to 1·82). Associations of variants in TNF, GSTP1 and CXCL8 genes with disease severity were identified, but were of low credibility. Conclusion: Genetic risk factors in genes related to trypsin activation and innate immunity appear to be associated with susceptibility to and severity of AP.